A bioecological perspective on talent identification in junior-elite soccer: A Pan-European perspective - Reeves, M. J.; Roberts, S. J. (Journal of Sports Sciences, 2020)
Elite soccer clubs across Europe spend ever-increasing sums of money on transfers and salaries for world-class players. Consequently, clubs` talent identification and development processes for junior players have become more professionalised. Based on a holistic ecological approach, this study presents an analysis of talent identification practices across some of the most productive soccer academies in Europe (N = 11). Data were collected via semi-structured interviews with 11 heads of academy recruitment from clubs in the "big five" European leagues. Clubs were purposively sampled based on their player productivity ranking. Interviews ranged from 52:26 minutes to 114:06 minutes in length (m = 87:53 ± 20.10 minutes). This study argues that holistic ecological approaches the environments were characterised through the interplay of factors that ranged from high-level internal to international level relationships. This resulted in the identification and recruitment of players from local and international environments. The purpose of recruitment was suggested to have a dual purpose: recruitment of players for the first team; recruitment of players for further development/monitoring and/or selling to another club.